Early Cretaceous Archaeamphora is not a carnivorous angiosperm - Wong, William Oki; Dilcher, David Leonard; Labandeira, Conrad C.; Sun, Ge; Fleischmann, Andreas (Frontiers in Plant Science, 2015)
Archaeamphora longicervia H.Q.Li was described as an herbaceous, Sarraceniaceae-like pitcher plant from the mid Early Cretaceous Yixian Formation of Liaoning Province, northeastern China. Here, a re-investigation of A. longicervia specimens from the Yixian Formation provides new insights into its identity and the morphology of pitcher plants claimed by Li. We demonstrate that putative pitchers of Archaeamphora are insect-induced leaf galls that consist of three components: (1) an innermost larval chamber with a distinctive outer wall; (2) an intermediate zone of nutritive tissue; and (3) an outermost zone of sclerenchyma. Archaeamphora is not a carnivorous, Sarraceniaceae-like angiosperm, but represents insect-galled leaves of the formerly reported gymnosperm Liaoningocladus boii G.Sun et al. from the Yixian Formation.